Mobilising demand for primary health care services among urban slums: insights from a case study in Bangladesh. Issue 6 (18th August 2021) - Adams, Alayne M.; Rashid, Sabina F.
ABSTRACT: This qualitative case study examines a pilot community mobilisation initiative to increase access to qualified primary health care services among slum dwellers in Bangladesh. Emerging from analysis are a series of key considerations in the design and implementation of mobilisation activities in poor urban settlements. These include who best to mobilise in highly stratified social settings; how to bridge communities in need with outside resources; the role of development agents in organising participation; whether mobilisation processes can be phased over time; and the imperative of policy advocacy to shift complex structural inequities that preclude investments in health care for the urban disadvantaged.